2022
DOI: 10.1155/2022/7111445
|View full text |Cite
|
Sign up to set email alerts
|

The Proinflammatory Cytokines IL-18, IL-21, and IFN-γ Differentially Regulate Liver Inflammation and Anti-Mitochondrial Antibody Level in a Murine Model of Primary Biliary Cholangitis

Abstract: Primary biliary cholangitis (PBC) is a cholestatic liver disease primarily featured by autoimmune-mediated damage of intrahepatic small- and medium-sized bile ducts. Elevated serum proinflammatory cytokines, serum anti-mitochondrial antibodies (AMAs), liver inflammation, and fibrosis are also hallmarks of PBC disease. However, whether the elevated proinflammatory cytokines play a role in autoimmune cholangitis remains unknown. Herein, we utilized the p40-/-IL-2Rα-/- PBC mouse model to investigate the roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…IL-21 is a cytokine produced by CD4 + T cells, and studies indicate that abnormal population of CD4 + T cells and upregulation of IL-21R signaling may play an important role in autoimmune disorders, such as systemic lupus erythematosus (SLE) [ 51 , 52 ]. Although a previous study suggested the potential association of IL-21 with PBC [ 53 ], functional roles of the IL-21/IL-21R axis in PBC and autoimmune disorders are still undefined. Further studies are required to conclude the association with PBC and elucidate functional roles of IL-21 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…IL-21 is a cytokine produced by CD4 + T cells, and studies indicate that abnormal population of CD4 + T cells and upregulation of IL-21R signaling may play an important role in autoimmune disorders, such as systemic lupus erythematosus (SLE) [ 51 , 52 ]. Although a previous study suggested the potential association of IL-21 with PBC [ 53 ], functional roles of the IL-21/IL-21R axis in PBC and autoimmune disorders are still undefined. Further studies are required to conclude the association with PBC and elucidate functional roles of IL-21 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…37 Anti-IFN-γ antibodies have demonstrated significant anti-fibrosis effects on liver injury models. 38 Studies on schistosomiasis confirmed that IFN-γ could reduce liver fibrosis in mice infected with schistosomiasis through regulating Th cell subsets. 39 We also found that the addition of C3 significantly reduced the serum IFN-γ and the ratio of IFN-γ/IL-4 in mice, suggesting that C3 may promote schistosomiasis liver fibrosis through regulating the balance of Th1/Th2.…”
Section: Discussionmentioning
confidence: 98%
“…As an immunomodulatory and anti‐fibrosis Th1‐type cytokine, IFN‐γ can significantly inhibit the growth of HSC and downregulate the expression of fibro‐related proteins such as IV‐C and α‐SMA in cells 36 which may be related to the promotion of Smad2 phosphorylation and the antagonism of TGF‐β 37 . Anti‐IFN‐γ antibodies have demonstrated significant anti‐fibrosis effects on liver injury models 38 . Studies on schistosomiasis confirmed that IFN‐γ could reduce liver fibrosis in mice infected with schistosomiasis through regulating Th cell subsets 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in dnTGF-βRII mice, IL-23, IL-17, and IL-6 were found to modulate anti-gp210 generation [ 34 ]. Additionally, a recent study in the p40 −/− IL-2Rα −/− PBC murine model suggested that cytokines such as IL-21 or IFN-γ were responsible for AMA levels [ 35 ]. Therefore, we hypothesize that fluctuations in autoantibody concentration may be a concomitant state of the disease and may reflect interference with the immune system under UDCA treatment to some extent.…”
Section: Discussionmentioning
confidence: 99%